1986
DOI: 10.1002/1097-4679(198605)42:3<520::aid-jclp2270420319>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological deficits in active licensed professional boxers

Abstract: Young, active, licensed professional boxers (N = 19) were found to display a pattern of neuropsychological deficits consistent with the more severe punch‐drunk syndrome of years past. These deficits resulted in significantly lower test performance than that of control athletes (N = 10) matched for race, age, and level of education. Tests that showed significant differences between groups include subtests of the Quick Neurological Screening Test, subtests of the Halstead‐Reitan Neuropsychological Test Battery, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…However, both Murelius and Haglund24 and Thomassen et al 23 found a slightly slower finger motor function of the non-dominant hand particularly with boxers having a high number of bouts. Interestingly Drew et al 15 found a similar result with professional boxers. Murelius and Haglund24 however make it clear that despite the slight difference, the boxers' performance on this task was 'well within normal range'.…”
mentioning
confidence: 70%
“…However, both Murelius and Haglund24 and Thomassen et al 23 found a slightly slower finger motor function of the non-dominant hand particularly with boxers having a high number of bouts. Interestingly Drew et al 15 found a similar result with professional boxers. Murelius and Haglund24 however make it clear that despite the slight difference, the boxers' performance on this task was 'well within normal range'.…”
mentioning
confidence: 70%
“…The overall effect (d ) of "exposure" as measured by examining the correlation between length of participation and neuropsychological functioning was .71 ( p , .05) based on four effect-size estimates, Q (3) 5 32, p , .05. In these studies, exposure was determined by number of boxing bouts and0or length of career (Drew et al, 1986;Murelius & Haglund, 1991), or frequency of heading in soccer (Abreau et al, 2000;Downs & Abwender, 2002). As there were so few of these correlational studies, they were not examined any further.…”
Section: Overall Effect Sizementioning
confidence: 99%
“…19 This suggests a consistency of exposure variables, permitting future comparison and use of Australian figures in determining prevalence rates of chronic boxing related brain injury. Unfortunately, similar demographic data are not available from the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%